A Critical Review of Standardized Measures of Hypnotic Suggestibility. Issue 1 (2nd January 2021) - Acunzo, David J.; Terhune, Devin B.
ABSTRACT: The most well-established finding gleaned from decades of experimental hypnosis research is that individuals display marked variability in responsiveness to hypnotic suggestions. Insofar as this variability impacts both treatment outcome in therapeutic applications of hypnosis as well as responsiveness to suggestions in experimental contexts, it is imperative that clinicians and researchers use robust measures of hypnotic suggestibility. The current paper critically evaluates contemporary measures of hypnotic suggestibility. After reviewing the most widely used measures, we identify multiple properties of these instruments that result in the loss of valuable information, including binary scoring and single-trial sampling, and hinder their utility, such as the inclusion of suboptimal suggestion content. The scales are not well-suited for contemporary research questions and have outlived their usefulness. We conclude by outlining ways in which the measurement of hypnotic suggestibility can be advanced.